PERENCANAAN PENGEMBANGAN PENERBANGAN PERINTIS: STUDI KASUS 2013 PADA SUATU AIRLINES - Nugroho Soebandrija, Khristian Edi; Nurlatifah, Raisa (Industrial and Systems Engineering Assessment Journal (INASEA), 2014)
This study discusses the Pioneer Flight Development Planning, within the scope of the case studies in 2013 at an airline in Indonesia. Economic growth that is followed by the growth of air traffic growth certainly helps to improve both foreign tourists and local tourists. However, there are still some areas in Indonesia that still has a low connectivity or it could be said that has no connectivity. To overcome this, the government is required to hold a pioneering air transport as set out in Article 104 of Law No. I, year of 2009. The theory used in this study related to the preparation of air velocity diagram, budget planning, project feasibility evaluation, and preparation of income statement. The analysis in this pioneering flight route includes route of the development of targeted pioneering flight, such as KPA-Ternate with the route of Ternate-Gebe, Ternate-Mangole, Ternate-Labuha, Ternate-Morotai, Ternate-Galela, Mangole-Sanana, and NAC Paludengan Buol, Palu -Tolitoli, Palu-Tarakan and Palu- Samarinda. The result is expected to be a reference and it was likely a reference to other studies and further, especially for the development and contribution to the Republic of Indonesia.